Social movements and collective behavior: an integration of meta-analysis and systematic review of social psychology studies - da Costa, Silvia; Páez, Dario; Martí-González, Mariacarla; Díaz, Virginia; Bouchat, Pierre (Frontiers in Psychology, 2023)
Background The impact of social movements (SMs) and collective behavior (CB) supports the relevance of approaching this phenomenon from social psychology. Several systematic reviews (10) and meta-analyses (6) have been carried out in the 21st century, but there is a lack of integration. Aim This study seeks to review the patterns of CB and corroborate the psychosocial factors that explain participation in CB and SMs, as well as the long-term psychological effects of participating in them. Method A systematic search was carried out in the databases Web of Science, Scopus, ProQuest, ScienceDirect, Willey Online Library, EBSCO, and JSTOR for articles dated between 1969 and 2022. We searched for meta-analyses and systematic reviews that empirically evaluated social movements and collective behavior. Of the 494 initial records, after scanning and eligibility phases, 16 meta-analyses and systematic reviews were analyzed in the present work. Results The evidence reviewed shows that participation in collective gatherings and CB are common. A cross-cultural survey suggests that collective gatherings are mostly of a leisure type, to a lesser extent religious and sporting, and to an even lesser extent, demonstrations and large religious rites. World Value surveys found that one to three persons out of 10 participate in protests or CB related to SMs and four out of 10 movements achieved some kind of success. Studies challenged that CBs were characterized by unanimity of beliefs, identification and behavior, generalized excitement, as well as mass panic and riot after catastrophes. Only two out of 10 CB are violent. Meta-analysis and systematic reviews confirm that participation in CB and SMs was associated with (a) intergroup conflict and realistic threat (r = 0.30); (b) positive attitudes, expectations, or agreement with goals or collective motive (r = 0.44); (c) cognitive fraternal relative deprivation (r = 0.25); (d) collective efficacy (r = 0.36); (e) collective identity (r = 0.34); (f) emotions and affective relative deprivation (r = 0.35); (g) moral conviction and threat to moral (r = 0.29); and (h) disagreement with system justification belief (r = −0.26). Participation in successful CB and SMs provokes positive changes in emotions, social identity and social relationships, values and beliefs, and empowerment, as well as negative effects such as depression, stress, burnout, and disempowerment related to the failures of SMs. Conclusion Studies confirm the importance of explanatory factors for SMs, with data from various cultural regions. There is a lack of systematic studies of CB as well as meta-analyses and more culturally diverse studies of the effects of participation in them.